Mathematical models of nonlinear consensus: time-invariant and time-varying cases - Saburov, Mansoor (2015)
In this keynote address, we shall present a time-invariant (varying) nonlinear model (rule or protocol) of discrete-time MAS. Our model is a generalization of the classical time invariant DeGroot model. Based on our proposed time-invariant model, we show a consensus in the discrete-time MAS. It seems that, unlike a linear case, a consensus can be easily achieved in a nonlinear case.